Manual of Digital Earth 2019
DOI: 10.1007/978-981-32-9915-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Big Data and Cloud Computing

Abstract: Big data emerged as a new paradigm to provide unprecedented content and value for Digital Earth. Big Earth data are increasing tremendously with growing heterogeneity, posing grand challenges for the data management lifecycle of storage, processing, analytics, visualization, sharing, and applications. During the same time frame, cloud computing emerged to provide crucial computing support to address these challenges. This chapter introduces Digital Earth data sources, analytical methods, and architecture for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Furthermore, the result also revealed that big data help in teaching strategy analysis. This agrees with [9] that the ultimate goal of using big data in education is to help educators formulate teaching strategies and analyze the collected information of learners to explore the functions of various components of the learning system and to analyze learner learning outcomes and teaching strategies. Addendum, [18] also corroborated that the prospects of big data are to analyze and summarize the teaching strategies to provide more effective teaching strategies in the field of education.…”
Section: Discussion Of Findingssupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, the result also revealed that big data help in teaching strategy analysis. This agrees with [9] that the ultimate goal of using big data in education is to help educators formulate teaching strategies and analyze the collected information of learners to explore the functions of various components of the learning system and to analyze learner learning outcomes and teaching strategies. Addendum, [18] also corroborated that the prospects of big data are to analyze and summarize the teaching strategies to provide more effective teaching strategies in the field of education.…”
Section: Discussion Of Findingssupporting
confidence: 82%
“…Lots of educational institutions have shown that analytics can facilitate student achievement, finance, interest as well as appropriate resource distribution and utilization [11]. [9] state that analytics is used in the planning, staffing, administration, supervision and financial plan. The prospective advantage of analytics in education is to estimate the expenditure to complete a programme (such as diploma and degree); school undertakings that have not been recognized as well as resource optimization.…”
Section: Concept and Benefit Of Big Data In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, distributed frameworks suffer from many limitations in terms of data sharing, processing scalability, and interactive performance Li et al. ( 2020 ). Besides, existing cloud solutions have limited support to the visualisation of the GIS big data Wang et al.…”
Section: General Stdm Challenges and Research Gapsmentioning
confidence: 99%